2016
DOI: 10.1073/pnas.1607548113
|View full text |Cite
|
Sign up to set email alerts
|

Covariation of axon initial segment location and dendritic tree normalizes the somatic action potential

Abstract: In mammalian neurons, the axon initial segment (AIS) electrically connects the somatodendritic compartment with the axon and converts the incoming synaptic voltage changes into a temporally precise action potential (AP) output code. Although axons often emanate directly from the soma, they may also originate more distally from a dendrite, the implications of which are not wellunderstood. Here, we show that one-third of the thick-tufted layer 5 pyramidal neurons have an axon originating from a dendrite and are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
124
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(139 citation statements)
references
References 46 publications
12
124
3
Order By: Relevance
“…Given the lack of a strong synaptic innervation at the AIS itself, synaptic regulation of dopaminergic neurons may be facilitated by innervation of regions near the AIS, specifically those of the axon bearing dendrite, which in both dopaminergic and hippocampal neurons (Blythe et al, 2009;Hamada, Goethals, de Vries, Brette, & Kole, 2016) has been shown to be particularly important for action potential generation and neuronal excitability.…”
Section: Ultrastructural Characterization and Synaptic Innervationmentioning
confidence: 99%
“…Given the lack of a strong synaptic innervation at the AIS itself, synaptic regulation of dopaminergic neurons may be facilitated by innervation of regions near the AIS, specifically those of the axon bearing dendrite, which in both dopaminergic and hippocampal neurons (Blythe et al, 2009;Hamada, Goethals, de Vries, Brette, & Kole, 2016) has been shown to be particularly important for action potential generation and neuronal excitability.…”
Section: Ultrastructural Characterization and Synaptic Innervationmentioning
confidence: 99%
“…In some studies, distal displacement of the AIS is associated with decreased excitability (Grubb 33 and Burrone, 2010; Hatch et al, 2017; Lezmy et al, 2017;Wefelmeyer et al, 2015). In others, neurons 34 with more distal AIS have an identical (Thome et al, 2014) or slightly hyperpolarized threshold 35 (Hamada et al, 2016). Thus, it is challenging to experimentally isolate the specific contribution of AIS 36 geometry to excitability changes.…”
Section: Introduction 20mentioning
confidence: 99%
“…Also, a recent study from the SĂŒdhof laboratory described a tight relationship between dendritic size, axonal growth and ankyrinG density at the AIS in neurons after L1CAM conditional deletion (Patzke et al, 2016). Moreover, a very recent study demonstrates that AIS distance to the soma in cortical layer 5 pyramidal adult neurons inversely correlates with dendritic complexity (Hamada et al, 2016), supporting the idea that dendritic morphology and AIS might be regulated in a coordinated manner in several neuronal types. Taking these studies and our results into account, change in dendritic morphology induced by CB1R lack of function is the more plausible hypothesis to explain AIS changes.…”
Section: Discussionmentioning
confidence: 72%